Centres for People with Intellectual Disabilities: Attendees' Perceptions of Benefit. Issue 6 (2nd September 2015) - Gajewska, Urszula; Trigg, Richard
Abstract : Background: Day and community learning centres aim to provide intellectually disabled (ID) people with social support, life skills and greater control over their lives. However, there is little research exploring the benefits of attendance from the perspective of attendees and whether these goals are met. Materials and methods: Unstructured interviews were held with four female and three male participants with a mild level of disability, from an East Midlands Mencap facility. Interviews were transcribed and analysed through the Grounded Theory approach. Results: Themes of social support, life skills, control and self‐image emerged from the transcripts. This brief report focuses on issues of self‐image and internal control of behaviour and emotion, as these constructs have received less attention within existing literature. Conclusions: Learning centres provide important psychological benefits for people with learning difficulties. These are often less accessible to evaluation, but are nonetheless key outcomes from the perspective of attendees.